Basic research on the primary prevention of boxing-related sports injuries with the development of a quantitative motion analysis software - Nakamura, K.; Uchida, M.; Sato, T. (Journal of Physical Therapy Science, 2021)
Purpose: To develop a quantitative motion analysis software specific to boxing (Fist Tactics Support) and to verify its effectiveness based on the percentage of hits that land on the participants. Participants and Methods: A total of 24 male professional boxers were divided into two groups: those who used Fist Tactics Support to analyze fight videos and instituted training changes based on the results (Fist Tactics Support group, 12 participants) and those who did not (controlgroup,12 participants). The overall percentage of hits that landed on the participants in the fights was compared between the two groups and betweenpre- and post-intervention. Results: There were no significant differences between the two groups; however, the percentage of hits that landed on the boxers of the Fist Tactics Support group was significantly lower at post-intervention than at pre-intervention. Conclusion: The use of scientific analysis results in boxing may facilitate the primary prevention of sports injuries.